OPERATING LEVERAGE AND FINANCIAL PERFORMANCE OF LISTED MANUFACTURING FIRMS IN KENYA - Obonyo Awuor Esther; Gordon Opuodho; Linus Isaac Ochieng (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Leverage is a critical determinant of financial performance in manufacturing firms due to the high proportion of fixed operating costs in capital-intensive production. In Kenya, listed manufacturing firms operate in a volatile environment characterized by fluctuating demand, cost uncertainty, and competitive pressures, making operating leverage a key strategic concern. While higher operating leverage can enhance profitability during periods of revenue growth, it may also increase earnings volatility and business risk during economic downturns. This study examines the effect of operating leverage on the financial performance of listed manufacturing firms in Kenya. A descriptive quantitative research design was adopted, guided by trade-off theory and operating leverage theory. The study employed a census approach, using secondary panel data from audited financial statements of firms listed on the Nairobi Securities Exchange over the period 2014–2023. Financial performance was measured using return on assets (ROA), while operating leverage was proxied by the degree of operating leverage (DOL). Panel regression analysis was conducted following diagnostic tests to ensure model robustness. The findings reveal that operating leverage has a positive and statistically significant effect on financial performance. Higher operating leverage improves profitability during periods of sales growth but also increases earnings volatility under declining demand. The study highlights the importance of optimizing cost structures and provides insights for managers, investors, and policymakers in enhancing firm resilience.